O debate sobre a (des)criminalização do aborto e suas implicações para a saúde pública no Brasil - Félix, Andressa Barboza (2018)
It addresses the debate about the (dis)criminalization of abortion in Brazil and its impacts on the public health. The present study aimed to analyze and discuss some of the main aspects that surround the abortion theme – historical, biophysiological and psychosocial, legal – and the relationship between induced abortion and public health. The methodology used consisted of bibliographical research in relevant publications on the subject and its aspects, including books and scientific articles, national and foreign, mostly made available electronically. Several legal sources were also consulted, in particular the Constitution of the Federative Republic of Brazil of 1988, the Penal Code and the Civil Code, as well as international treaties and conventions, ordinary laws and other norms present in the brazilian legal system. In addition, official morbidity and mortality data were collected that indicate the clandestine practice of abortions in Brazil, extracted from the DATASUS system of the Ministry of Health. Finally, an analysis of the results of the research and brief considerations on the theme conclude this work, as well as indicate, based on what was verified and discussed in this study, that the decriminalization and consequent enlargement of the hypotheses of legalized abortion are not appropriately compatible with public health in Brazil.